2020
DOI: 10.1097/mph.0000000000001853
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Core Binding Factor Acute Myeloid Leukemia in Children: A Single-Center Experience

Abstract: Childhood acute myeloid leukemia (AML) harboring core binding factor (CBF)–associated translocations are considered as a favorable cytogenetic subgroup. The 2 major subtypes of CBF-AML include t(8;21) and inversion of chromosome 16, accounting for ∼25% of patients. Because of expensive and toxic treatment, which may require hospitalization during the entire course of induction chemotherapy, most of the centers in Pakistan neither workup for this low-risk entity nor offer curative treatment. Therefore, we adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Interestingly, the percentage of chloroma was lower in patients with inv(16) than those with t(8; 21), and this was never been reported before. In accordance with previous studies, when referred to relapse, BM relapse and CNS relapse were more frequent in patients with inv(16) than those with t(8; 21) [ 7 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the percentage of chloroma was lower in patients with inv(16) than those with t(8; 21), and this was never been reported before. In accordance with previous studies, when referred to relapse, BM relapse and CNS relapse were more frequent in patients with inv(16) than those with t(8; 21) [ 7 9 ].…”
Section: Discussionsupporting
confidence: 92%
“… 26 In another study, in acute myeloid leukaemia, nearly 25% of the patients showed the core-binding factor associated with translocations. 27 In the USA, recent germline genomic studies have revealed that at least 5%–10% of children with cancer and nearly 3%–4% with acute lymphoblastic leukaemia, develop the disease due to an underlying genetic predisposition. 28 Further, in a report from China, the two most important factors identified for childhood leukaemia are exposure to hydrocarbons and ionising radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Median overall survival (OS) of favorable group was 51 (range 20-79) weeks (95%CI 41. 3 weeks (95% CI 38.6 to 49.3), respectively. There was no statistical different of survival rate between favorable and unfavorable groups (P value of DFS and OS were 0.161 and 0.120, respectively) (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…The CBF-AML includes 2 major subtypes of favorable group, translocation t(8;21)(q22;q22), and inversion of chromosome 16 (inv(16)(p13q22)), which together account for 25% of pediatric de novo AML patients. 3 Berlin-Frankfurt-Munster (BFM) study groups and Medical Research Council (MRC) haves confirmed the overall survival (OS) rate of t(8;21) and inv(16) mutation in childhood CBF AML were 91% and 92%, respectively. 4 This study was conducted to evaluate the role of karyotype abnormalities t(8,21) and inv(16) as favorable prognostic factors of complete remission after induction phase chemotherapy in pediatric AML.…”
mentioning
confidence: 98%